Smile with diabetes: reflections on illness perception and diabetes management behaviors of adolescents in private health care in South Africa - Deacon, Elmari (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background: The association between illness perception and diabetes management has been well established in adults but is not clearly understood for adolescents. This article reflects on qualitative findings on illness perception from the perspective of adolescents, and suggests future research to operationalize findings. Methods: Qualitative document analysis was conducted on four research projects forming part of the Smile with Diabetes project, which aims to investigate psychosocial variables in diabetes management, including illness perception, within the adolescent and youth populations. Thematic analysis was used to derive four themes from the qualitative and review studies examined in the document analysis. Results: The voices of the adolescents were evident as four prominent themes: 1) living with diabetes leads to a sense of being different; 2) integration of diabetes into identity is critical, but difficult to achieve; 3) fear of potential negative consequences motivates adherence to treatment; 4) diabetes management is difficult, but possible. Conclusions: The findings not only confirmed the importance of illness perception in the management of diabetes by adolescents, but also indicate that illness perceptions should be investigated from a developmental perspective, specifically taking identity development into consideration in this group. Adolescents should be made aware of how their thinking about diabetes and its management affects their experience of living with diabetes and its future management. This study further contributes to the literature by focusing on the patient’s voice in understanding living with a chronic condition, and reassures that positive outcomes are possible when living with a chronic condition such as diabetes.